Democratic Assemblage: Power, Normativity, and Responsibility in More-than-Human Participation - Asenbaum, Hans; Bussu, Sonia (Theoria (Pietermaritzburg), 2025)
Over the past two decades, the scholarly community interested in participatory and deliberative democracy has focused their attention on democratic innovations. Designs such as participatory budgets and citizens assemblies have been conceptualised as the actualisation of democratic ideals in a micro setting, in relative isolation from each other and the wider society (Bussu et al. 2022). In recent years the attention of democracy scholarship turned toward the connectivity between various democratic innovations and raised questions about their political and societal impact (Dean et al. 2019; Jaquet et al. 2023; Parry et al. 2021). The deliberative systems approach (Mansbridge et al. 2012) makes important steps towards understanding connectivity by exploring the transmission between public space, where democratic innovations are located, and empowered space, where governments reside (Dryzek 2009). However, both democratic innovations and deliberative systems are too often conceptualised in relatively static terms. Systems imply clear structures, and democratic innovations tend to apply expert-generated design that intends to guide human interaction. This view pays limited attention to the role of materiality and more-than-human world – including physical space, objects, technology, nonhuman animals, weather phenomena, etc. – in democratic participation.